ROMANIA’S ECONOMIC GROWTH IN THE CURRENT INTERNATIONAL CONTEXT - Ion Viorel MATEI (Annals of Spiru Haret University Economic Series, 2011)
Present and future economic growth is increasingly dependent on trends in the global economy. They lead to an intertwining of the economic progress at a national-regional-global level. In particular to bearing economic integration, globalization, globalization of economic, political multipolarity, expanding economy on a continental and global level, etc. The effects of these changes can be both beneficial and negative, so we proposed a study on the evolution of parameters characterizing both economic growth and the evolution of this growth in Romania in the current international context.